Serum aluminum in 176 feline patients with application to the diagnostic approach to a tremoring patient with kidney disease receiving aluminum hydroxide therapy - Rachel Sheffler; Stephanie Karpf; Sarah Rebolloso; Vicki Miksicek; John P. Buchweitz; Birgit Puschner (BMC Veterinary Research)
Abstract Background Control of circulating phosphorus concentrations in patients with chronic kidney disease is a mainstay of treatment and may include use of aluminum hydroxide as an intestinal phosphate binder. Serious complications of excess aluminum reported in dogs and man include encephalopathy, microcytic anemia, osteomalacia, and regional myopathy at serum concentrations exceeding 100 ng/mL. Reports of aluminum toxicosis are not available for cats receiving aluminum hydroxide and circulating aluminum concentrations are poorly characterized. The aim of this study is to establish therapeutic and toxic serum aluminum concentrations in cats and apply this data to an intoxication case. Results Of cats with CKD who received aluminum hydroxide, 9/21 serum samples exceeded aluminum concentrations of 100 ng/mL. After removal of outliers, 18 cats with kidney disease who received aluminum hydroxide had mean serum aluminum concentrations of 69 ng/mL [95% CI: 42–97 ng/mL], which was significantly higher than mean aluminum concentrations in cats not receiving aluminum hydroxide (p = 0.0034). The mean aluminum concentration of 141 feline serum samples not receiving aluminum hydroxide was 29 ng/mL [95% CI: 24–33 ng/mL]. Of the 141 samples, 16 cats presenting for wellness or dental procedures had mean concentrations of 36 ng/mL [95% CI: 15–56 ng/mL]. This data was applied to a case of a 16-year-old spayed female domestic shorthair with IRIS stage 2 chronic kidney disease with a 7-month history of mild hindlimb weakness and intermittent right forelimb myoclonus. The patient received oral aluminum hydroxide, and the serum contained 376 ng/mL of aluminum suggestive of toxicosis. Resolution of clinical signs was noted following a switch to an aluminum-free phosphate binding medication, and, at 5-month follow-up, the serum aluminum concentration was 71 ng/mL. Conclusions Our data suggest that serum aluminum concentrations in cats exceeding 86 ng/mL can result in clinical aluminum toxicosis and is comparable to the 100 ng/mL toxic threshold described in humans. The data provided facilitate the diagnostic assessment of cats receiving aluminum hydroxide supplementation. Veterinarians must recognize the toxic effects of aluminum and pursue diagnostic testing in suspect cases to mitigate invasive and costly workup for aluminum-associated clinical signs or euthanasia due to deterioration of these patients.